Improving Life Quality of Postmenopausal Women with Oral Health Advancement - Nurdiana, Nurdiana; Wulandari, Pitu; Amalia, Martina (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2022)
Menopause is a natural developmental stage in a woman's life that is marked by permanent cessation of menstruation. The period after menopause is called postmenopausal. Menopause causes irreversible hormonal changes. Hormones have a potential role in the development and integrity of the oral cavity. Changes in the oral cavity and the vulnerability of postmenopausal women to oral abnormalities due to decreased reproductive hormones, make this to be an important concern by providing information, education, and motivation as well as prevention of oral abnormalities in postmenopausal because if the oral disease is left untreated can affect systemic conditions and interfere with the quality of life of postmenopausal women. In this regard, this community service carried out counseling to add information, examination of the oral cavity to educate, as well as good and correct brushing practices to increase motivation for prevention of oral abnormalities. After this community service, participants became more aware of the condition of their mouth and had the motivation to improve the condition of their oral cavity through information obtained from counseling, oral examination, and tooth brushing practices. Furthermore, this activity needs to be carried out on an ongoing basis and conduct training of trainers (ToT) for village midwives as health workers who directly interact with the community.